Criminalising Hate Law as Social Justice Liberalism - Walters, Mark Austin (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book presents both a new theoretical framework for the criminalisation of hate, referred to as "law as social justice liberalism", and a comprehensive analysis of hate crime laws that have been enacted globally. The book begins by reflecting back on 30 years of theorisation on hate crime laws, arguing that there has been a failure to adequately capture the distinct harms of hate-based criminal conduct within legal frameworks. The book posits that liberal societies interested in advancing social equality ought to expand conventional paradigms of harm used in criminal law by comprehending hate-based conduct as a form of social injustice. Drawing on the work of Iris Young, the book sets out a comprehensive analysis of the harms of hate crime as a form of group-based oppression and uses this to set out criteria for the inclusion of protected characteristics under legislation. The second half of the book presents findings from a comparative study of hate crime laws enacted in 190 different legal jurisdictions. This includes a new taxonomy of types, models and legal tests used by legislatures to capture the myriad forms of hate-based criminal conduct that occur globally. Further evaluation of case law and empirical research on the application of these diverging legislative approaches is used to provide recommendations on how legislators ought to construct hate crime laws. The book completes its analysis of law as social justice liberalism by synthesising law, punishment and restorative justice as a means of ensuring that liberal systems of "justice" are more firmly anchored to the advancement of "social justice". Mark Austin Walters is Professor of Criminal Law and Criminology at the University of Sussex, UK. Mark's research interests are focused primarily on hate crime studies and more broadly on criminal law theory and criminal justice reform, including restorative justice practice and theory.
Introduction -- Chapter 1: Criminal Law as "Social Justice Liberalism" -- Chapter 2: Social Justice Liberalism and The Criminalisation of Hate -- Chapter 3: Who should be protected by hate crime laws and why? -- Chapter 4: Defining hate crime law globally: Models of legislation -- Chapter 5: Should hate crime laws mean punishing people more?. Chapter 6: Conclusions.
Keywords: Critical criminology; Law and the social sciences; Political sociology; Criminal law; Corrections; Punishment; Critical Criminology; Socio-Legal Studies; Critical Criminology; Political Sociology; Criminal Law and Criminal Procedure Law; Prison and Punishment